Targeting multiple pathogenic mechanisms with polyphenols for the treatment of Alzheimer’s disease: Experimental approach and therapeutic implications - Jun eWang; Jun eWang; Weina eBi; Alice eCheng; Daniel eFreire; Prashant eVempati; Wei eZhao; Bing eGong; Elsa eJanle; Tzu-Ying eChen; Mario eFerruzzi; James eSchmeidler; et al. (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disease of aging and currently has no cure. Its onset and progression are influenced by multiple factors. There is growing consensus that successful treatment will rely on simultaneously targeting multiple pathological features of AD. Polyphenol compounds have many proven health benefits. In this study, we tested the hypothesis that combining three polyphenolic preparations (grape seed extract, resveratrol and Concord grape juice extract), with different polyphenolic compositions and partially redundant bioactivities, may simultaneously and synergistically mitigate amyloid-β (Aβ) mediated neuropathology and cognitive impairments in a mouse model of AD. We found that administration of the polyphenols in combination did not alter the profile of bioactive polyphenol metabolites in the brain. We also found that combination treatment resulted in better protection against cognitive impairments compared to individual treatments, in J20 AD mice. Electrophysiological examination showed that acute treatment with select brain penetrating polyphenol metabolites, derived from these polyphenols, improved oligomeric Aβ (oAβ)-induced long term potentiation (LTP) deficits in hippocampal slices. Moreover, we found greatly reduced total amyloid content in the brain following combination treatment. Our studies provided experimental evidence that application of polyphenols targeting multiple disease-mechanisms may yield a greater likelihood of therapeutic efficacy.